2017
DOI: 10.1021/jacs.7b07574
|View full text |Cite
|
Sign up to set email alerts
|

Combining in Vitro and in Silico Single-Molecule Force Spectroscopy to Characterize and Tune Cellulosomal Scaffoldin Mechanics

Abstract: Cellulosomes are poly-protein machineries that efficiently degrade cellulosic material. Crucial to their function are scaffolds consisting of highly homologous cohesin domains, which serve a dual role by coordinating a multiplicity of enzymes as well as anchoring the microbe to its substrate. Here we combined two approaches to elucidate the mechanical properties of the main scaffold ScaA of Acetivibrio cellulolyticus. A newly developed parallelized onepot in vitro transcription-translation and protein pulldown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 49 publications
3
63
1
Order By: Relevance
“…Single-molecule force spectroscopy has been employed previously to distinguish the nature of proteinligand bonds (37) and hence infer multi-modality or conformational transitions involved in protein-ligand binding interactions (50). Single-molecule force spectroscopy in conjunction with steered MD simulations has been employed extensively to study superior mechanical stability (51), characterize the force-unfolding behavior (52), and resolve multiple binding modes of cohesin-dockerin complexes (53). However, the application of AFM-based force spectroscopy to study CBM-cellulose binding has revealed challenges in distinguishing specific vs non-specific interactions (54).…”
Section: Discussionmentioning
confidence: 99%
“…Single-molecule force spectroscopy has been employed previously to distinguish the nature of proteinligand bonds (37) and hence infer multi-modality or conformational transitions involved in protein-ligand binding interactions (50). Single-molecule force spectroscopy in conjunction with steered MD simulations has been employed extensively to study superior mechanical stability (51), characterize the force-unfolding behavior (52), and resolve multiple binding modes of cohesin-dockerin complexes (53). However, the application of AFM-based force spectroscopy to study CBM-cellulose binding has revealed challenges in distinguishing specific vs non-specific interactions (54).…”
Section: Discussionmentioning
confidence: 99%
“…These unfolding force determined here are also comparable to previous results. 28,29 Moreover the mechanical resilience of the extremely high-affinity KD ~ fM interaction of a bacteriocin (colicin E9) and its immunity protein (Im9) was probed [30][31][32] . The E9:Im9 system is particularly suitable for the tethered complex approach: ColicineE9 is a fast endonuclease that kills bacteria rapidly by shredding their chromosome, recombinant expression in E. coli thus is challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Only a one protein species can be fused reliably to the tip. Using tethered complexes, one can probe many different interactions with the same high-strength handle on the cantilever by swapping the tethered complex on the surface 29 . In addition, if the ultrastable handle is very reliable -as the CohE:Xdoc -it can serve as a proxy for non-refolding and sensitive complexes.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the stability of the best structural models, we performed another set of SMD simulations using the 5 best models as initial structures in what we call an in silico force-spectroscopy approach 34 . Using a wide-sampling strategy, 200 steered molecular dynamics (SMD) replicas were carried out for a total of 4 µs for each binding mode, using the 5 different initial structures.…”
Section: Homology Modeling and Molecular Dynamics Simulationsmentioning
confidence: 99%